The CEO Characteristics Factors Toward Tax Aggressiveness Of Family Companies In Indonesia - Rachmawati Meita Oktaviani; Kukrit Wicaksono; Sunarto Sunarto; Ceacilia Srimindarti (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This study examines the relationship between the characteristics of the CEO that has an effect toward tax aggressiveness of family companies in Indonesia. Purposive sampling is done to get samples, there are 70 samples with 280 total observations. Estimation model test is used in determining the proper estimation model regression, after all, REM is chosen as the estimation model. The study results that CEO tenure and risk preferences has an effect toward tax aggressiveness of family companies while educational background of CEO has no significant effect toward tax aggressiveness. More than 95% of companies in Indonesia are family companies. Government should do any actions to maximize state tax revenue. This study adds CEO risk preference as the development of prior research in order to examine another variable that might has an effect toward tax aggressiveness of family companies in Indonesia.